Methanolic extract from the fruit kernel of Mangifera indica (Anacardiaceae) improves blood count, serum iron levels and transaminases in anemic rats - Tiepka, Wawa Justine; Yao, N'guessan Alain; Konan, Kouakou S.; Touré, Abdoulaye (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Mangifera indica (Anacardiaceae), known for its many therapeutic potentialities is used in traditional Ivorian medicine to treat anemia. The aim of this study was to evaluate the effects of methanolic extract from the fruit kernel of Mangifera indica (EMMI) on blood pressure, iron and transaminase levels in rat’s anaemic by phenyl hydrazine (50 mg/kg, per os). Methods: The determination of iron, tannins, polyphenols and total flavonoids in EMMI samples was performed, using specific reagents. Different groups of rats were treated with EMMI (100, 500 and 1000 mg/kg) or Folifer (50 mg/kg) by gavage for 14 days. The determination of hematological and biochemical parameters following the different treatments was carried out, using an URIT 3000 PLUS machine. Results: Phytochemical analyses show that EMMI (10 mg/ml), is rich in polyphenols (38.97±0.04 mg GAE/g), flavonoids (26.83±0.02 mg QE/g), tannins (33.87±0.06 mg TAE/g). and iron (52.91±0.01 mg/100 g). The observed anti-anaemic effects were dose-dependent. After 14 days of treatment, EMMI (1000 mg/kg) induced normalization of RBC, Hb, Hct and serum iron levels (p<0.001), with a decrease in ASAT and ALAT levels respectively of about 28 and 34% in anaemic rats (p<0.001). These effects were comparable to those of Folifer (p>0.5). Conclusion: Altogether, this study showed that EMMI normalizes blood count, serum iron and transaminases in rats made anaemic by administration of phenyl hydrazine. This beneficial effect would be attributed to its richness in secondary metabolites and iron.